Executive Function in Adolescents with Fetal Alcohol Spectrum Disorders: A Developmental Perspective - Pomario, Tania (Department of Psychiatry and Mental Health, 2025)
Objective: Children with fetal alcohol spectrum disorders (FASD) have well-documented deficits in executive function. However, few previous studies have examined executive deficits displayed by children with FASD within a developmental framework. This longitudinal study explored the manifestation of executive function in both alcohol-exposed and typically developing adolescents from a low socioeconomic community in a low-and middle-income country. Method: 110 participants (48 with FASD, mean age 14.65 years, SD = 0.65 and 62 controls, mean age 14.49 years, SD = 0.44) were assessed at two time points, 18 months apart. Participants completed a battery of neuropsychological tests to measure executive function. Parents and teachers provided ratings of participants’ everyday executive function on the Behavior Inventory of Executive Function (BRIEF). Principal component analysis examined the underlying components of the neuropsychological measures of executive function in the control group. Composite executive function test scores were computed for both groups, and ANCOVA was used to examine whether a) cognitive performance of the FASD group differed from that of the control group, and b) whether there was a change in scores across the two time points. Chi-square and ANCOVA analyses assessed group differences on the BRIEF. Finally, correlations and regressions investigated whether composite cognitive scores were significant predictors of behaviour, as measured by the BRIEF. Results: Neuropsychological measures of executive function clustered into four distinct factors reflecting the domains of Generativity, Attentional Control, Working Memory, and Processing Speed. The FASD group performed significantly worse than the control group on the Working Memory domain (p < .01). On the BRIEF, a significantly higher proportion of the FASD group was rated as having scores in the clinically impaired range by both parents (p < .001) and teachers (p < .01) compared to controls. Significant differences were found between the FASD and control groups on the Emotional Control and Organization of Materials scales of the BRIEF Teacher. Significant differences were found for the Global Executive Composite and the Plan/Organize and Monitor scales on the BRIEF Parent. The cognitive composites Attentional Control and Generativity were significantly negatively correlated with scores on several of the BRIEF Teacher clinical scales for the FASD group. Conclusion: Performance on working memory tasks emerged as the only domain of executive function that distinguished the FASD group from the control group. There was no notable developmental change in executive abilities over the course of the 18- month period in either group. Both parents and teachers reported that the FASD group displayed significantly more executive deficits, but only teacher ratings were correlated with neuropsychological test results. This suggests that children with FASD have more difficulties with executive functioning in their everyday lives than what is being detected on neuropsychological measures alone. Keywords: fetal alcohol spectrum disorder, executive function, Behavior Rating Inventory of Executive Function, adolescents, longitudinal study